- 7
- 0
In the expression:
ksp = (3.42 x 10^-7) (6.84 x 10^-7)^2
= 1.6 x 10^-19
I don't understand how the final answer is found. Can someone show me a step by step? I'm attempting to understand how to do these types of questions! Any help is greatly appreciated!
ksp = (3.42 x 10^-7) (6.84 x 10^-7)^2
= 1.6 x 10^-19
I don't understand how the final answer is found. Can someone show me a step by step? I'm attempting to understand how to do these types of questions! Any help is greatly appreciated!